The institutional economy : demand and supply - Reisman, David A. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
The institutional economy is the economy of rules and laws, conventions and precedents. It will be of interest to all social scientists concerned to make demand and supply more relevant to the economic conditions of the present day
Contents: 1. Introduction 2. Economy as Society 3. Present as Past 4. Society as Past 5. People and Things 6. Benevolence 7. Malevolence 8. Needs and Wants 9. The Demand to Supply 10. Organisational Order 11. Organisational Cost 12. Conclusion Bibliography Index
Includes bibliographical references (p. 253-265) and index.
Keywords: Institutional economics